SPORT MARKETING - Omer Špirtović; Danilo Aćimović; Ahmet Međedović; Zoran Bogdanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Word "marketing" comes from AngloSaxon linguistic domain and implies in a narrow sense the market. Under marketing, we consider certain process, which should create and solve relations of exchange between manufacturers on one side, and consumers on the other. Discussion about sport marketing implies its theoretical definition and generalization, and then its actual definition in sport environment. Sport marketing belongs to business function of sport organization and represents primaly an economical process of connecting produktion (sport organizations with sportsmen and coaches) and consumption (sport and other public). Sport marketing is the reality in sport today, and cannot be observed as fashionabless of capitalistic production. Today is almost impossible for sport organization to make business without its business part called sport marketing if it wants to survive in sport arena.